COVID-19 환자를 간호한 간호사의 외상 후 스트레스와 이직의도의 관계에서 소명의식의 조절효과 - 우민주; 박부경 (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2025)
연구목적: 본 연구의 목적은 COVID-19 환자를 간호한 간호사의 외상 후 스트레스와 이직의도 관계에서 소명의식의 조절효과를 알아보는 것이다. 연구방법: D시에 소재한 3개 대학병원에서 COVID-19 환자를 간호하는 간호사 151명으로부터 자료를 수집하였다. 대상자들은 외상 후 스트레스(IES-R-K), 소명의식(CVQ-R) 및 이직의도에 대해 자가 보고식 설문조사를 시행하였다. SPSS 25.0을 이용하여 기술통계, t-test, one-way ANOVA, Scheffe test, Pearson 상관계수, 계층적 다중회귀분석을 시행하였다. 연구결과: 외상 후 스트레스, 소명의식, 이직의도의 평균 점수는 각각 0.83±0.70, 1.51±0.71, 2.89±1.10이었다. 외상 후 스트레스는 소명의식(r=.20, p=.011), 이직의도(r=.29, p=.001)와 양의 상관관계를 보인 반면, 소명의식은 이직의도(r=-.17, p=.029)와 음의 상관관계를 보였다. 소명의식은 외상 후 스트레스와 이직의도의 관계에서 조절효과가 있는 것으로 나타났다(β=-.16, p=.032). 결론: 소명의식은 외상 후 스트레스와 이직의도의 관계에서 조절효과가 있는 것으로 나타났다. 따라서 외상 후 스트레스 간호사의 이직을 예방하기 위해서는 간호사의 소명의식을 강화하는 프로그램을 개발하고 적용할 필요가 있다. Purpose: This study aimed to examine the moderating effect of calling on the relationship between post-traumatic stress and turnover intention among nurses caring for COVID-19 patients. Methods: Data were collected from 151 nurses caring for COVID-19 patients at three university hospitals located in D City. Participants completed selfreported online surveys on post-traumatic stress (IES-R-K), calling (CVQ-R), and turnover intention. Descriptive statistics, t-tests, one-way ANOVA, Scheffé test, Pearson's correlation coefficients, and hierarchical multiple regression were performed using SPSS 25.0. Results: The mean scores of post-traumatic stress, calling, and turnover intention were 0.83±0.70, 1.51±0.71, and 2.89±1.10, respectively. Post-traumatic stress had positive correlations with calling (r=.20, p=.011) and turnover intention (r=.29, p=.001), whereas calling had a negative correlation with calling and turnover intention (r=-.17, p=.029). Calling had a moderating effect in the relationship between post-traumatic stress and turnover intention (β=-.16, p=.032). Conclusion: Calling has a moderating effect on the relationship between post-traumatic stress and turnover intention. Therefore, developing and implementing a program is necessary to strengthen nurses' perceptions of calling to prevent nurses with post-traumatic stress from leaving their jobs. KCI Citation Count: 0